2023
DOI: 10.3390/cells12141810
|View full text |Cite
|
Sign up to set email alerts
|

Cell Transitions Contribute to Glucocorticoid-Induced Bone Loss

Abstract: Glucocorticoid-induced bone loss is a toxic effect of long-term therapy with glucocorticoids resulting in a significant increase in the risk of fracture. Here, we find that glucocorticoids reciprocally convert osteoblast-lineage cells into endothelial-like cells. This is confirmed by lineage tracing showing the induction of endothelial markers in osteoblast-lineage cells following glucocorticoid treatment. Functional studies show that osteoblast-lineage cells isolated from glucocorticoid-treated mice lose thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Either unpaired 2-tailed Student's t test or one-way ANOVA with Tukey's multiplecomparisons test was used to analyze for statistical significance. We used pwr R package to calculate the size of the effect and the statistical power as previously described [23]. The number of animals in each group was sufficient to reach more than 80% power to identify differences in the results.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Either unpaired 2-tailed Student's t test or one-way ANOVA with Tukey's multiplecomparisons test was used to analyze for statistical significance. We used pwr R package to calculate the size of the effect and the statistical power as previously described [23]. The number of animals in each group was sufficient to reach more than 80% power to identify differences in the results.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, it was shown that a shift of osteoblast lineage cells toward endothelial differentiation was induced by glucocorticoids and that this unwanted cell transition caused osteoblast lineage cells to lose osteogenic capacity, thereby contributing to glucocorticoidinduced bone loss [23]. The study also showed that glucocorticoids suppress Osterix expression but activate Foxc2 in osteoblast lineage cells to switch the cell fate and functional capacity, contributing to osteoporosis [23]. Here, we unveil a new interaction between the glucocorticoid receptor and aurora A in controlling the plasticity of osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations